1967
DOI: 10.1099/00221287-49-1-139
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium-limited Growth of Bacillus subtilis, in Pure and Mixed Cultures, in a Chemostat

Abstract: SUMMARYThe influence of Mg2+-limitation on the growth of a typical Gram-positive organism-Bacillus subtilis-was investigated and the data compared with that obtained with Aerobacter aerogenes grown under similar conditions. The magnesium contents of both organisms varied with growth rate but were very similar at corresponding growth rates. With Mg2+-limited chemostat cultures of each organism, uptake of Mg2+ was almost complete at specific growth rates less than 0.7 x maximum. Cellular Mg2+ was tightly bound, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
1

Year Published

1968
1968
1981
1981

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 9 publications
2
28
1
Order By: Relevance
“…We reported previously (Tempest, Dicks & Meers, 1967) that the affinities with which Bacillus subtilis and Aerobacter aerogenes cell walls bound magnesium ions were different, and that this difference correlated with the ability of the Gram-negative organisms to outgrow the bacilli in Mg2+-limited mixed cultures in a chemostat. The above mentioned adsorption experiments were made with organisms grown in Mg2+-limited culture only; but since the wall composition of organisms is known to vary with the chemical nature of the environment (Ellwood & Tempest, 1967;Tempest, Dicks & Ellwood, I 968), it was of interest to determine whether the affinity with which organisms bound Mg2+ at their surfaces also varied with changes in the nature of the growth limitation.…”
Section: Introductionmentioning
confidence: 99%
“…We reported previously (Tempest, Dicks & Meers, 1967) that the affinities with which Bacillus subtilis and Aerobacter aerogenes cell walls bound magnesium ions were different, and that this difference correlated with the ability of the Gram-negative organisms to outgrow the bacilli in Mg2+-limited mixed cultures in a chemostat. The above mentioned adsorption experiments were made with organisms grown in Mg2+-limited culture only; but since the wall composition of organisms is known to vary with the chemical nature of the environment (Ellwood & Tempest, 1967;Tempest, Dicks & Ellwood, I 968), it was of interest to determine whether the affinity with which organisms bound Mg2+ at their surfaces also varied with changes in the nature of the growth limitation.…”
Section: Introductionmentioning
confidence: 99%
“…The continuous culture experiments indicated that Mg2+ content, bacterial dry weight, S-factor production and extracellular carbohydrate, as well as intracellular protein and carbohydrate contents, are all dependent both on the Mg2+ content of the medium and on the growth rate, while the change in RNA content is independent of Mg2+ content and reflects only the bacterial growth rate. A similar series of experiments measuring protein, carbohydrate and RNA content in Klebsiella (Aerobacter) aerogenes and Bacillus subtilis (Tempest et al, 1965(Tempest et al, , 1967 showed the same tendency, but the percentage differences obtained were smaller than those reported here. A change to Mg2+-limited growth results in morphological and chemical changes in Cytophaga sp.…”
Section: A B O V a L L I U Smentioning
confidence: 58%
“…jluorescens have more efficient mechanisms for the uptake of magnesium from their environment than the Gram-positive organisms listed above. It is important to point out that S. epidermidis would grow only in simple salts media that had been supplemented with Casamino acids (I %, w/v) and yeast extract (0.001 %, w/v), each of which contain substances that stimulated growth and the uptake of magnesium by B. subtilis (Tempest et al 1967) and presumably also by the Staphylococcus organisms. Nevertheless, S. epidermidis cultures still were rapidly outgrown by either A. aerogenes or P. fEuorescens organisms.…”
Section: Resultsmentioning
confidence: 99%
“…Continuous cultures of organisms were maintained in 0.25 1. chemostats (designed by Dr D. Herbert) without pH control. The magnesium-limited medium was basically that described previously (Tempest et al, 1967), but the magnesium content was varied as indicated in the Results section. The potassiumlimited medium was that described by Tempest, Dicks & Hunter (1966)~ but with the potassium concentration decreased to 0-1 5 mM ; the carbon-limited medium was that of Tempest, Hunter & Sykes (1965) but with glucose ( I g./l.)…”
mentioning
confidence: 99%
See 1 more Smart Citation